The Multiple Sclerosis Severity Score: fluctuations and prognostic ability in a longitudinal cohort of patients with MS. Issue 1 (March 2019) - Gross, RH; Sillau, SH; Miller, AE; Farrell, C; Krieger, SC
Background: The Multiple Sclerosis Severity Score (MSSS), combining the Expanded Disability Status Scale (EDSS) and disease duration, attempts to stratify multiple sclerosis (MS) patients based on their rate of progression. Its prognostic ability in the individual patient remains unproven. Objectives: To assess the stability of MSSS within individual persons with MS in a longitudinal cohort, to evaluate whether certain factors influence MSSS variability, and to explore the ability of MSSS to predict future ambulatory function. Methods: A single-center retrospective review was performed of patients following a single provider for at least 8 years. Mixed model regression modeled MSSS over time. A Kaplan–Meier survival plot was fitted, using change of baseline MSSS by at least one decile as the event. Cox modeling assessed the influence of baseline clinical and demographic factors on the hazard of changing MSSS by at least one decile. Linear models evaluated the impact of baseline EDSS, baseline MSSS, and other factors on the Timed 25-Foot Walk (T25FW). Results: Out of 122 patients, 68 (55.7%) deviated from baseline MSSS by at least one decile. Final T25FW had slightly weaker correlation to baseline MSSS than to baseline EDSS, which was moderately strongly correlated with future log T25FW. Conclusion: Individual MSSS scores often vary over time. Clinicians should exercise caution when using MSSS to prognosticate.